Research on Situation Awareness Model of Information Content Security Incidents in Telecommunication Network - Lin Ge; Xinsheng Ji; Tao Jiang (Dianxin kexue)
Aiming at the main features of the information content security incidents and telecommunication network themselves，a design of situation awareness model was presented.The model using distributed character data collection and hierarchical progressive integration，the status of security situation of the whole telecommunication network was analyzed.According to the structure of model，hierarchical information fusion proximate calculation based on evidence theory was used to resolve the problem of how to use the initial information to determine the probability in high level information fusion.The simulation results show that the model can compute fast in real time in high accuracy，and it can perceive and determine the incidents effectively.